Evidence Best Evidence Rule - Miller, Colin (Open textbook library., 2012)
The Best Evidence Rule, contained in Article X of the Federal Rules of Evidence (Rules 1001-1008) and state counterparts, is a Rule that requires a party seeking to prove the contents of a writing, recording, or photograph to produce the original (or a duplicate) or account for its nonproduction. Through a series of cases and hypotheticals drawn from actual cases, this chapter gives readers a roadmap for how to address any Best Evidence Rule issue in practice. Faculty materials also available: In addition to the free, open learning materials for students listed above, this eLangdell chapter includes a teacher's manual. Faculty and staff at CALI member schools can access these materials by logging in to eLangdell with a cali.org username and password. Contact CALI.